Is There a (Host) Genetic Predisposition to Progressive Multifocal Leukoencephalopathy? - Hatchwell, Eli (Frontiers in Immunology, 2015)
Progressive Multifocal Leukoencephalopathy (PML) has been described in association with a variety of predisposing risk factors, including HIV/AIDS, lymphoproliferative disorders and, most recently, treatment with a range of biologics, most notably natalizumab in Multiple Sclerosis (MS). However, while these underlying disorders appear to be (usually) necessary, they are not sufficient to predict the development of PML, since only a fraction of such individuals will succumb, raising the question of whether host genetic factors must also play a role. Evidence is mounting that this is, indeed, the case but more work needs to be done to fully delineate these underlying genetic factors.